Amino acid and carbohydrate structural variants of glycoprotein products (M-N glycoproteins) of the M-N allelic locus. - Blumenfeld, O O (1981)
Major glycoprotein of MgM, MM Miltenberger III (MiIII), and M-N erythrocyte membranes from individual donors were cleaved with CNBr and their amino-terminal octapeptides were examined with respect to amino acid and carbohydrate composition. The amino-terminal octapeptides from the heterozygous MgM donor were resolved into two types, A and A'. MgM A was identical to octapeptide A from MM glycoproteins in carbohydrate and amino acid compositions. MgM A' exhibited amino acid composition similar to NN peptide A except for a single substitution of an Asx for a Thr and, as a result, was not glycosylated. MM(MiIII) octapeptide A was identical to M peptide A in amino acid composition, but differed in carbohydrate content. This glycopeptide contained three O-glycosidically linked carbohydrate units, one of which contained GlcNAc bound to a core of NeuAc, Gal, and GalNAc. About two such units were also present in the CNBr glycopeptide B of the glycoprotein, and on the basis of studies with alkaline borohydride and alkaline sulfite degradations, these units are believed to have the following structure: (formula see text) The Mg is an allelomorph of the M-N locus, likely evolved from a single base substitution in the N gene. The resulting single amino acid substitution effects the posttranslational carbohydration of neighboring Ser and Thr residues. The MM(MiIII) appears to be a product of the M gene that undergoes sequences of posttranslational glycosylations different from those of the M-N glycoproteins.